Efek Jus Semangka Terhadap Jumlah Dan Motilitas Spermatozoa Tikus Wistar Yang Dipapari MSG - Sufitni; Tengku Muhammad Reza Syahputra; Muhammad Ichwan (HEALTH CARE : JURNAL KESEHATAN, 2019)
Background: MSG is a glutamic acid uses as a food flavoring especially processed food products. MSG in processed foods can exceed the estimated levels because some processed foods do not put on the packaging label. Some studies report the effects of MSG on various organs, especially the testes. Long-term and excessive consumption of MSG causes testicular damage due to oxidative stress resulting in lipid peroxidation. Antioxidants in watermelons play a role in preventing oxidative damage. Aim: to find out the effect of watermelon juice on the number and motility of sperm exposed to MSG. Method: Experimental research design of post test only control group, 35 male Wistar rats were randomly divided into five groups: KN(pellet), KP(MSG 10mg/grBB), P1(MSG 10mg/grBB + watermelon juice 25%), P2(MSG 10mg/grBB + watermelon juice 50%), P3(MSG 10mg/grBB + watermelon juice 100%). Rats were treated for 30 days, then killed and taken vas deferens used to check sperm count and motility. Result: The KP group experienced a decrease in the number and motility of spermatozoa. There was a significant difference in the number(p=0,009) and motility(p=0,003) spermatozoa of the KP group compared to KN. There was a significant difference in the motility of the P3 group(p=0,040) compared to the KP. There was an improvement in motility in groups P1, P2, and P3 which approached KN. Conclusion: The administration of MSG showed significant results on the number and motility of spermatozoa. Giving watermelon juice can improve the number and motility of spermatozoa exposed to MSG.